An Analysis of Errors in the Use of Simple Present Tense in Descriptive Text Written by Students at SMKN 5 Palu - S, Sakina; Manurung, Konder; Nadrun, Nadrun; Bochari, Siska (Journal of English Language and Education, 2025)
Grammar proficiency is vital for effective writing in English, particularly concerning the simple present tense in descriptive texts. While numerous studies have documented common grammatical errors, a gap exists in understanding the specific errors made by students at SMKN 5 Palu. This research aimed to identify and classify the types of errors made by tenth-grade students in their use of the simple present tense in descriptive texts and to determine the most prevalent error types. Employing a quantitative descriptive approach and Dulay's Surface Strategy Taxonomy, data were collected from 15 students through their written texts. The findings indicated that omission errors were the most frequent, accounting for 57.97% of total errors, followed by missordering errors at 8.70%. These results highlight significant challenges with subject-verb agreement and the correct application of auxiliary verbs. The study concludes that enhancing grammar instruction and incorporating error analysis can substantially improve students' writing proficiency. These findings underscore the need for targeted interventions in grammar education to address specific error patterns and enhance overall writing skills.